Synthesis and spectroscopic and biological activity for binuclear complexes with Mn(II),Fe(II) and Zn(II) with ligand type N2O2 (Journal of the College of Basic Education, 2022)
In this work, the m-phenylene diamine and resorcinol have been used in the synthesis ligand [m-phenylene bis(azo resorcinol)] tetradentate type (N2O2). The tetra dentate ligand was reacted with the metal ions Mn(II),Fe(II)and Zn(II )in (2:2) mole ratio via reflux in Ethanol using Et3N as a base to give binuclear complexes of genral formula [M2(L)2(H2O)4]. The synthesized compounds were characterized by spectroscopic methods [I.R, UV-VIS and A.A] along with melting point, chloride content and conductivity measurements. These studies revealed an octahedral geometries for Mn(II) , Fe(II) and Zn(II) complexes. The ligand and its complexes exhibited biological activity against the Bacillus(G+) strain and the E.coli(G-) strain.